2023
DOI: 10.1038/s41598-023-27659-4
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia modified albumin can act as an independent predictor of inhospital mortality in patients with acute aortic dissection

Abstract: Acute aortic dissection (AAD) is a serious disease characterized by high mortality. However, there are no accurate indicators to predict in-hospital mortality. The objective of this study was to identify the potential value of ischemia modified albumin (IMA) in prediction of in-hospital mortality of AAD patients. This was a single-center, prospective study involved 314 patients undergoing AAD, including 197 males and 117 females, aged 26–87 (57.14 ± 21.71) years old, 116 cases of TAAD and 198 cases of TBAD (37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…ATAAD is a rapidly progressing aortic disease with a high mortality rate ( 2 , 3 ). Without timely intervention, mortality can increase by 1%–2% per hour within 48 h, reaching approximately 90% in 1 week ( 4 ). Population-based studies have shown that up to half of individuals affected with ATAAD die before reaching the hospital ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…ATAAD is a rapidly progressing aortic disease with a high mortality rate ( 2 , 3 ). Without timely intervention, mortality can increase by 1%–2% per hour within 48 h, reaching approximately 90% in 1 week ( 4 ). Population-based studies have shown that up to half of individuals affected with ATAAD die before reaching the hospital ( 5 ).…”
Section: Introductionmentioning
confidence: 99%